(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: Nowadays CT scan is done in most head injury cases. The patients who do not survive are subjected to further investigations in the form of post-mortem examination. In most cases a correlation can be shown between the reported CT scan findings and post-mortem findings. However, in few cases the lesion may be misdiagnosed or remain undiagnosed by CT scan examination. Aim : • Comparison of ante–mortem CT scan findings with post–mortem autopsy findings. To compare our present study data with other studies. Methodology: The study was conducted with 255 cases of fatal head injury registered in Post–Mortem Register and autopsied at Forensic Medicine and Toxicology department, Indira Gandhi Medical College and Research Institute, Puducherry. The details likes scalp injuries, type of skull fracture, brain injury and intracranial Haemorrhage were recorded. Evaluation was done for the cases available with CT scan findings.